2020
DOI: 10.1073/pnas.1913851117
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements shape visual learning

Abstract: Most people easily learn to recognize new faces and places, and with more extensive practice they can become experts at visual tasks as complex as radiological diagnosis and action video games. Such perceptual plasticity has been thoroughly studied in the context of training paradigms that require constant fixation. In contrast, when observers learn under more natural conditions, they make frequent saccadic eye movements. Here we show that such eye movements can play an important role in visual learning. Obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
(81 reference statements)
2
9
0
Order By: Relevance
“…As a manifestation of plasticity occurring in the adult brain, VPL has significant practical and theoretical implications. For subjects with normal visual acuity, VPL can shed light on fundamental processes, such as perceptual development (Gibson, 1969;Gibson & Pick, 2003) and the formation of visual expertise (Appelbaum & Erickson, 2018;DeLoss, Watanabe, & Andersen, 2015;Deveau, Ozer, & Seitz, 2014;Laamerad, Guitton, & Pack, 2020;Reingold & Sheridan, 2011). There is also evidence that VPL can improve outcomes and be used as a strategy for visual rehabilitation in aging and clinical populations (Campana, Camilleri, Pavan, Veronese, & Lo Giudice, 2014;DeLoss et al, 2015;Huxlin, Martin, Kelly, Riley, Friedman, Burgin, & Hayhoe, 2009;Liao, Gichira, Wang, & Chen, 2015;Maniglia, Cottereau, Soler, & Trotter, 2016;Maniglia, Pavan, Sato, Contemori, Montemurro, Battaglini, & Casco Hayhoe, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a manifestation of plasticity occurring in the adult brain, VPL has significant practical and theoretical implications. For subjects with normal visual acuity, VPL can shed light on fundamental processes, such as perceptual development (Gibson, 1969;Gibson & Pick, 2003) and the formation of visual expertise (Appelbaum & Erickson, 2018;DeLoss, Watanabe, & Andersen, 2015;Deveau, Ozer, & Seitz, 2014;Laamerad, Guitton, & Pack, 2020;Reingold & Sheridan, 2011). There is also evidence that VPL can improve outcomes and be used as a strategy for visual rehabilitation in aging and clinical populations (Campana, Camilleri, Pavan, Veronese, & Lo Giudice, 2014;DeLoss et al, 2015;Huxlin, Martin, Kelly, Riley, Friedman, Burgin, & Hayhoe, 2009;Liao, Gichira, Wang, & Chen, 2015;Maniglia, Cottereau, Soler, & Trotter, 2016;Maniglia, Pavan, Sato, Contemori, Montemurro, Battaglini, & Casco Hayhoe, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental preparation has been described in a previous publication 21 . In brief, high-resolution T1 and T2-weighted anatomical MRIs (0.6-0.8 mm 3 voxels) were acquired for each animal and were used for surgical planning. Animals were implanted with a custom titanium head post (Hybex Innovations, Montreal Canada) using standard sterile surgical techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Even for simple tasks, such as discriminating the orientation of a line, behavioral changes often emerge after days or weeks of practice (Watanabe & Sasaki, 2015). For more complex tasks, such as the detection of anomalies in medical images, efficient performance requires months or years of training (Reingold & Sheridan, 2011;Laamerad, et al, 2020). Neurophysiological studies have similarly revealed that the adult visual cortex often changes very slowly, if at all, in response to experience (Yang & Maunsell, 2004;Ghose & Maunsell, 2002;Schoups, et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, individual neurons respond to visual stimuli at specific positions, but they alter their encoding of space when an eye movement is being planned (Duhamel et al, 1992; Neupane et al, 2016a,b; Sommer & Wurtz, 2006; Nakamura & Colby, 2002). This perisaccadic remapping is thought to play a variety of roles in perception (Cicchini et al, 2013), memory (Umeno & Goldberg, 2001), and learning (Laamerad et al, 2020).…”
Section: Introductionmentioning
confidence: 99%